The Hidden Indonesian Language Literacy Curriculum In Arabic Language Textbooks For Islamic Junior High School - Sodiq, Syamsul; Alindah, Lutfiyah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Many religious-based schools and universities in Indonesia have widely implemented Arabic language textbooks as a learning material. However, Arabic is often considered challenging to learn due to its distinct linguistic origin from the Indonesian language. Therefore, there is a need for effective methods to facilitate students in learning Arabic just as they learn Indonesian. Surprisingly, a covert approach to learning Indonesian is also applied to studying Arabic. There are influential Arabic language textbooks that teach Indonesian grammar implicitly. This research aims to analyze the presence of curriculum of Indonesian language literacy in Arabic language textbooks, mainly for grades VII, VIII, and IX in Indonesian Islamic Junior High Schools (Madrasah Tsanawiyah or MTs). These textbooks were published by the Ministry of Religious Affairs of the Republic of Indonesia in 2020. The research method used is a qualitative descriptive approach, which involves content analysis of each chapter in these three books. The research findings reveal a significant amount of Indonesian language literacy content in Arabic textbooks. This content appears as explanations that serve as material clarification for students. Notably, the Indonesian language explanations account for 10% of the grade VII textbooks and 2% of the grade VIII and IX textbooks. Three forms of Indonesian language literacy content were successfully identified: language for comprehension introduction, comparison, and grammar contextualization.